2007
DOI: 10.1007/s00586-007-0401-3
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intraobserver reliability assessment of the Cobb angle: manual versus digital measurement tools

Abstract: The objective of this study is to determine the intraobserver and interobserver reliability of end vertebra definition and Cobb angle measurement using printed and digital radiographs of 48 patients with scoliosis. The Cobb angle and the end vertebra were assessed by six observers in 48 patients with scoliosis using printed and digital radiographs. Definition of end vertebra and measurement of the Cobb angle was repeated three times with a 3 week interval. Intraclass correlation coefficients (ICC) were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
128
1
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 197 publications
(153 citation statements)
references
References 12 publications
9
128
1
15
Order By: Relevance
“…The intraobserver reliability for the Cobb angle found in this study was nearly the same for both methods (mean ICC radiographs, 0.978; mean ICC 3D CT images, 0.961). The variability and reliability of Cobb angle measurement in 3D CT images described in the present study are comparable to the results previous studies reported for manual or digital measurement of plain radiographs [7,22]. We measured the Cobb angle with predefined end vertebrae because it has been shown that the reliability is higher when the error of end plate selection is limited [7].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The intraobserver reliability for the Cobb angle found in this study was nearly the same for both methods (mean ICC radiographs, 0.978; mean ICC 3D CT images, 0.961). The variability and reliability of Cobb angle measurement in 3D CT images described in the present study are comparable to the results previous studies reported for manual or digital measurement of plain radiographs [7,22]. We measured the Cobb angle with predefined end vertebrae because it has been shown that the reliability is higher when the error of end plate selection is limited [7].…”
Section: Discussionsupporting
confidence: 89%
“…Despite this technical support, an inaccuracy in angle measurement persists due to a disadvantage of the Cobb method itself. Inter-and intraobserver variabilities of approximately 3-5°h ave been published [4,7]. Another systematic bias is that there is a high variability in end vertebra selection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the change had no clinical impact when evaluated by SRS-22 scores. Based on our previous study, the coefficient of variations for intra-observer measurement was 2.3 % for the MT curve [6] using a digital measurement software on appropriately adjusted X-ray films [7,8], and by selecting the same end vertebra in each patient at different time course [9]. In this study, we also used CT scans to demonstrate the correction loss in the axial plane and, in doing so, we tried to minimize measurement errors caused by patient positioning during CT examination using the relative AVR (rAVR), which was defined as the difference between the axial rotation angle of the upper instrumented vertebra and the apical vertebra.…”
mentioning
confidence: 99%